Meta-Analysis of Neurochemical Changes Estimated via Magnetic Resonance Spectroscopy in Mild Cognitive Impairment and Alzheimer's Disease - Liu, Huanhuan; Zhang, Dandan; Lin, Huawei; Zhang, Qi; Zheng, Ling; Zheng, Yuxin; Yin, Xiaolong; Li, Zuanfang; Liang, Shengxiang; Huang, Saie (Frontiers in Aging Neuroscience, 2021)
The changes of neurochemicals in mild cognitive impairment (MCI) and Alzheimer's disease (AD) patients had been observed via magnetic resonance spectroscopy in several studies. However, whether it exists the consistent pattern of changes of neurochemicals in the encephalic region during the progression of MCI to AD were still not clear. The study performed meta-analysis to investigate the patterns of neurochemical changes in the encephalic region in the progress of AD. We searched the PubMed, Embase, Cochrane Library, and Web of Science databases, and finally included 63 studies comprising 1086 MCI patients, 1256 AD patients, and 1907 healthy controls. It showed that during the progression from MCI to AD, N-Acetyl Aspartate (NAA) decreased continuously in posterior cingulate (PC) (SMD: -0.42 [95% CI: -0.62 to -0.21], z=-3.89, P<0.05), NAA/Cr (creatine) was consistently reduced in PC (SMD: -0.58 [95% CI: -0.86 to -0.30], z=-4.06, P<0.05) and hippocampus (SMD: -0.65 [95% CI: -0.97 to -0.34], z=-4.10, P<0.05), while Myo-inositol (mI) (SMD: 0.44 [95% CI: 0.26 to 0.61, z=4.97, P<0.05) and mI/Cr (SMD: 0.25 [95% CI: -0.01 to 0.50], z=1.92, P=0.055) were raised in PC. Furthermore, these results were further verified by a sustained decrease in the NAA/mI of PC (SMD: -0.94[95% CI: -1.24 to -0.65], z=-6.26, P<0.05). Therefore, the levels of NAA and mI were associated with the cognitive decline and might be used as the potentially biomarkers to predict the possible progression from MCI to AD.